Narrative Review: The Influence of Carcass Placement on Insect - Algazali, Mohamad Assegaf; Abid, Istiana Firqah (Photon: Jurnal Sain dan Kesehatan, 2024)
Forensic entomology is crucial in providing information related to insects and legal cases involving both animals and humans. Insects serve as indicators of the time of death, with their presence influenced by the cause and placement of the corpse. This study aims to examine the effect of carcass placement on insect arrival. The method used in this narrative review involves searching for articles with the same or similar topics to obtain data relevant to the topic under discussion. The results of this narrative review revealed that insects arriving on rabbit carcasses placed both indoors and outdoors, as well as on pig carcasses placed outdoors in Warri, Southern Nigeria, belong to seven orders: Diptera (Muscidae, Calliphoridae, Sarcophagidae, Formicidae, Tachinidae), Coleoptera (Chrysomelidae, Staphylinidae, Scarabaeidae, Silphidae, Cleridae, Dermestidae, Histeridae), Hymenoptera (Formicidae), Hymenoptera, Lepidoptera, Blataria, and Orthoptera (Grillidae). Additionally, the difference in placement affected larval growth, with carcasses placed in enclosed spaces showing higher larval growth compared to those placed in open spaces. Keywords: Forensic Entomology, Decomposition, Insects